The Relationship between Knowledge Level and Attitudes towards Sexually Transmitted Infectious Diseases - Abduh, Anniza Putri; Abdi, Dian Amelia; Surdam, Zulfiyah; Yunita, Lisa; Gayatri, Sri Wahyuni (Newinera Publisher, 2024)
Sexually Transmitted Infections (STIs) are infectious diseases that can be transmitted from one person to another through sexual contact. Cases of sexually transmitted infections (STIs) continue to increase, the phenomenon of increasing and spreading cases of sexually transmitted infections that occur in high risk groups is very fast, one of those most at risk is teenagers, because teenagers are a transition period from childhood to older age. As they mature, teenagers will become more curious about everything, including sexual matters. To determine the relationship between knowledge and attitudes towards sexually transmitted infections. This type of research uses the approach used is a cross sectional study. The research was conducted at the Indonesian Muslim University, Campus II Jalan Urip Sumoharjo KM.05, Faculty of Medicine, with the research taking place from May 2022 to October 2023. Based on the research results, it shows that the respondents studied in this study tend to have good knowledge about sexually transmitted infections. The respondents studied in this study tended to have a good attitude towards sexually transmitted infections. There was a significant relationship between knowledge and attitudes towards sexually transmitted infections among students of the 2021 Class of Indonesian Muslim University Makassar Medical Education Study Program.